High-rate polyanionic sodium battery positive electrode material prepared on basis of recycled lithium iron phosphate and preparation method of high-rate polyanionic sodium battery positive electrode material
The sodium iron phosphate dihydrate compound was recovered through the acid leaching-decomposition adjustment-precipitation reaction-drying process, and the sodium element and iron phosphate were uniformly mixed with sodium and iron phosphate to prepare high-rate polyanionic sodium electropositive electrode material, which solved the problem of recycling and utilization of the positive electrode powder of the retired lithium iron phosphate battery, and achieved efficient resource utilization and electrical performance improvement.
Patent Information
- Application Number
- CN202411718854.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art has failed to fully utilize the positive electrode powder in retired lithium iron phosphate batteries for recycling, resulting in waste of resources and scarcity of lithium resources.
Through the process of acid leaching-decomposition adjustment-precipitation reaction-drying, the positive electrode powder in the waste lithium iron phosphate battery is recovered and prepared into a high-purity sodium iron phosphate compound dihydrate, and by adding raw materials such as sodium sources and carbon sources multiple times, the sodium elements and iron phosphate are uniformly mixed to prepare a high-rate polyanionic sodium electropositive electrode material.
It realizes efficient utilization of the positive electrode powder of waste lithium iron phosphate battery, improves the electrical performance of sodium-electric positive electrode materials, and has a high resource utilization rate, solving the problem of lack of lithium resources.
Smart Images

Figure CN119660697A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of polyanion sodium positive electrode materials, and in particular relates to a method for preparing high-rate polyanion sodium positive electrode materials based on recycling lithium iron phosphate. Background Art
[0002] With the development of technology, lithium-ion batteries have become the most popular power batteries, among which lithium iron phosphate batteries are widely used in the field of electric vehicles due to their high energy density, long cycle life, good safety performance, etc. As the batteries are used and worn out, a large number of power batteries will face retirement. Therefore, how to properly handle retired lithium iron phosphate batteries is an urgent problem to be solved. For lithium batteries, the cost of positive electrode materials accounts for a high proportion, so how to efficiently recycle the positive electrode powder in lithium iron phosphate batteries is particularly important.
[0003] With the application and development of lithium-ion batteries, the problem of lithium resource shortage has gradually been exposed. However, sodium resources are abundant and easy to mine, making sodium-ion batteries a secondary battery with great application prospects. At present, the positive electrode materials of sodium-ion batteries mainly include layered transition metal oxides, Prussian blue analogs, and polyanion compounds. Among them, polyanion compounds are regarded as an ideal positive electrode material for sodium-ion batteries due to their stable structure and high safety performance. At present, the more studied polyanion sodium-ion battery positive electrode materials include Na 3 V 2 (PO4) 3 , NaVPO 4 F and other metal-based phosphates such as V-based phosphates and non-V-based metal-based phosphates. There are two main preparation processes for metal-based phosphates of this type of polyanion sodium-ion battery positive electrode materials: one is to use a solid-phase ball milling process to mix and ball-mill water-insoluble metal salts, sodium salts, phosphorus sources, vanadium sources (optional) and carbon sources (glucose, citric acid, sucrose, etc.), and then spray-dry to obtain a precursor powder, which is then calcined to obtain the final product. The other is to use a liquid-phase process to mix and dissolve water-soluble metal salts, sodium salts (sodium carbonate, sodium hydroxide, sodium oxalate, sodium phosphate, etc.), phosphorus sources (sodium pyrophosphate, diammonium phosphate, sodium phosphate, monohydrogen / dihydrogen phosphate, etc.), vanadium sources (optional) and carbon sources (glucose, citric acid, sucrose, etc.), and then spray-dry to obtain a precursor powder, which is then calcined to obtain the final product.
[0004] At present, the required raw materials are synthesized to prepare polyanion sodium cathode materials, but the lithium iron phosphate in the waste lithium iron phosphate batteries is not fully recovered for research, development and application. Therefore, recycling the lithium iron phosphate in the waste lithium iron phosphate batteries to prepare polyanion sodium cathode materials with excellent performance is a promising direction. Summary of the invention
[0005] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for preparing a high-rate polyanionic sodium cathode material based on recycling lithium iron phosphate, which can effectively improve the electrical properties of the prepared polyanionic sodium cathode material.
[0006] Technical solution: The present invention is based on the method of recycling lithium iron phosphate to prepare a high-rate polyanion sodium positive electrode material, comprising the following steps:
[0007] (1) Acid leaching of the cathode powder in the waste lithium iron phosphate battery and solid-liquid separation to obtain a leachate, iron powder is added to the leachate, and the reaction is filtered to obtain phosphorus-containing Fe 2+ filtrate;
[0008] (2) adding an oxidant to the filtrate for oxidation reaction, adjusting the molar ratio of Fe to P in the system to (1.02-1.1):1, adding sodium hydroxide solvent to adjust the pH value, and performing precipitation and aluminum removal reaction to obtain a suspension; filtering the suspension, acid washing and water washing to obtain a crude sodium iron phosphate compound;
[0009] (3) dispersing the crude sodium iron phosphate compound in water, adding phosphate and sodium salt to adjust the molar ratio of P, Fe and Na to 3: (2.8-3): (0.5-1.5), then stirring and crystallizing at 70-100° C. until the material turns crystal white, and then aging for 1-3 hours, separating the aged filter cake, and drying to obtain the sodium iron phosphate dihydrate compound;
[0010] (4) mixing sodium iron phosphate dihydrate compound with sodium salt, carbon source and vanadium source, adding water and stirring to obtain a dispersed suspension, and finally sand milling, spray drying and sintering to obtain a high-rate polyanion sodium positive electrode material; wherein the molar ratio of the added amount of the sodium salt to the sodium element in the sodium iron phosphate dihydrate compound is (1.5-2.5):(0.5-1.5).
[0011] The invention uses waste lithium iron phosphate electrode powder as raw material, and prepares high-purity sodium iron phosphate dihydrate through the process of acid leaching-impurity removal-component adjustment-precipitation reaction-drying, and uses sodium iron phosphate dihydrate as raw material to prepare vanadium-doped polyanion type sodium positive electrode material.
[0012] In the preparation process, sodium element is added in three processes respectively, that is, sodium source is added in three steps. The first time is the impurity removal stage, in which sodium hydroxide solution is used to adjust pH to remove aluminum element and crude sodium iron phosphate is prepared, and sodium element is wrapped in iron phosphate at the same time; the second time is the component adjustment process, in which sodium salt is used, and in the process of iron phosphate forming crystal nuclei in this process, the first sodium source entrained first enters the crystal nucleus first, and as the crystal nucleus grows and fuses, the sodium element added in this process will be wrapped in the iron phosphate crystal; the third time is the sand milling process of synthesizing sodium iron phosphate, in which the remaining part of sodium salt is added, and this part of sodium salt mainly supplements the sodium ions lacking in the molecular formula of sodium iron phosphate, and sodium iron phosphate is synthesized through sand milling, spray drying and sintering. The method can achieve uniform mixing of sodium element and iron phosphate at the atomic level, thereby improving the electrical properties of the finally synthesized sodium iron phosphate.
[0013] In addition, after the sodium source is introduced in the second step to form crystal nuclei, a sodium iron phosphate dihydrate compound is obtained. The compound has low strength and is easier to grind. Therefore, the sodium iron phosphate dihydrate and the sodium source, carbon source, and vanadium source in the third step can be ground into smaller particles, and the element uniformity is better.
[0014] Furthermore, in step (1) of the preparation method of the present invention, the acid solution includes at least one of phosphoric acid, sulfuric acid, nitric acid or hydrochloric acid, and the amount thereof is nFe:nH=1:(4-6); the amount of the iron powder added is niron powder:nCu in the leaching solution=(1-3):1.
[0015] Furthermore, in step (2) of the preparation method of the present invention, the amount of the oxidant added is n leachate (Fe 2+ ):nH 2 O 2 =1:(0.5~0.7).
[0016] Furthermore, in step (2) of the preparation method of the present invention, the sodium hydroxide solvent is added to adjust the pH value to 1.6-2.0, and the precipitation aluminum removal reaction is carried out at 20-50° C. for 0.5-2 h.
[0017] Furthermore, in step (3) of the preparation method of the present invention, the phosphate is monoammonium phosphate or phosphoric acid.
[0018] Furthermore, in step (3) and step (4) of the preparation method of the present invention, the sodium salt is sodium carbonate, sodium acetate, sodium citrate, sodium oxalate, sodium bicarbonate, sodium sulfate, sodium chloride or sodium nitrate.
[0019] Furthermore, in step (4) of the preparation method of the present invention, the amount of the carbon source added is 0 to 15% of the mass of the sodium iron phosphate dihydrate compound, and the carbon source is glucose, sucrose, starch, citric acid, oxalic acid or graphene.
[0020] Furthermore, in step (4) of the preparation method of the present invention, the molar ratio of the added amount of the vanadium source to the iron element in the compound of sodium iron phosphate dihydrate is (0-0.2):3, and the vanadium source is ammonium vanadate or ammonium metavanadate.
[0021] Furthermore, in step (4) of the preparation method of the present invention, the stirring time is 20 to 200 min, the stirring rate is 100 to 300 r / min; the sanding particle size is 0.2 to 0.6 μm, and the sanding temperature is 20 to 50°C; the spray particle size is 6 to 20 μm, and the spray outlet temperature is 70 to 110°C; the sintering temperature is 450 to 750°C, and the sintering time is 6 to 12 h.
[0022] The present invention is based on the high-rate polyanion sodium positive electrode material prepared by the above method, and the molecular formula of the sodium positive electrode material is Na 3-x Fe +2 3-x V x (PO4) 3 , where x=0~0.2.
[0023] Beneficial effect: Compared with the prior art, the significant advantages of the present invention are: the method first uses waste lithium iron phosphate electrode powder as raw material, and obtains sodium iron phosphate dihydrate compound through the process of acid leaching-impurity removal-ingredient adjustment-precipitation reaction-drying, and uses the sodium iron phosphate dihydrate as raw material to prepare high-rate polyanion sodium positive electrode material, thereby realizing efficient utilization of waste lithium iron phosphate electrode powder, and at the same time being able to achieve uniform mixing of sodium element and iron phosphate at the atomic level, thereby improving the electrical properties of the final synthesized sodium iron phosphate. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope image of the polyanionic sodium cathode material prepared in Example 1 of the present invention;
[0025] Figure 2 This is the XRD diagram of the polyanionic sodium cathode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0027] Example 1
[0028] The molecular formula of the polyanionic sodium positive electrode material prepared in Example 1 is Na 3 Fe 3 (PO4) 3 The preparation method comprises the following steps:
[0029] (1) 500 g of slag (referred to as ferrophosphorus slag) produced after lithium extraction from waste lithium iron phosphate battery black powder was taken, sulfuric acid with a concentration of 20% was added in an amount of nFe:nH=1:4, and stirred at 70°C and a stirring speed of 300 r / min for 3 h, and a leachate was obtained by solid-liquid separation; iron powder was added to the leachate for reaction within 30 min to remove copper, n iron powder (Fe): n leachate (Cu)=1.5:1, so that the trivalent iron in the system was completely reduced to divalent iron, and phosphorus-containing Fe was filtered out. 2+ filtrate.
[0030] (2) Phosphorus-containing Fe 2+ The filtrate was added with 10% hydrogen peroxide for 1 to 4 hours to oxidize all the divalent iron, among which n leachate (Fe 2+ ):nH 2 O 2 =1:0.7; phosphoric acid was added to adjust the system nFe:nP=1.05:1, sodium hydroxide was added to adjust the pH value to 1.8, and a precipitation reaction was carried out at a temperature of 30°C for 1 hour to obtain a suspension.
[0031] (3) The suspension is filtered through a plate and frame filter press to obtain a crude sodium iron phosphate compound, which is then washed twice with an acid having a pH value of 1.2 and then washed twice with water to obtain a crude sodium iron phosphate compound from which aluminum has been removed.
[0032] (4) At room temperature, the crude sodium iron phosphate compound obtained in step (3) is dispersed in deionized water with a solid-liquid ratio of 100 g / L; phosphoric acid and sodium carbonate are then added to adjust nP:nFe:nNa=3:3:1; the temperature is raised to 90°C and crystallized under stirring until the material turns white, and the aging reaction is carried out for 2 hours, and the aged filter cake is separated.
[0033] (5) Drying the aged filter cake obtained in step (4) at 120° C. for 6 h to obtain a sodium iron phosphate dihydrate compound.
[0034] (6) Mixing sodium ferric phosphate dihydrate with sodium carbonate and sucrose, adding water to control the solid content to 40%, stirring the mixture for 20 to 200 minutes at a stirring rate of 100 to 300 r / min to obtain a dispersed suspension; wherein the molar ratio of the added amount of sodium salt to the sodium element in the sodium ferric phosphate dihydrate compound is 2:1, and the added amount of the carbon source is 10% of the mass of the sodium ferric phosphate dihydrate compound.
[0035] (7) The suspension described in step (6) is subjected to sand grinding, spray drying, and sintering to obtain a high-rate polyanion sodium positive electrode material; wherein the sand grinding particle size is controlled to be 0.2-0.4 μm, and the sand grinding temperature is 40° C.; the inlet air temperature of the spray drying is 270° C., the exhaust air temperature is controlled to be 80° C., and the spray particle size is controlled to be 6-20 μm to obtain a spray material.
[0036] (8) Sintering the spray material described in step (7) under nitrogen protection at 500° C. for 10 h to obtain a high-rate polyanion sodium cathode material.
[0037] The sodium positive electrode material prepared by the present invention was characterized by scanning electron microscopy and element composition, and the obtained structure is as follows Figure 1 and Figure 2 As shown. Figure 1 It can be seen that the synthetic material is spherical and has fine pores on the surface; Figure 2 It can be seen that the presence of sodium, iron and phosphorus was verified in the sodium battery positive electrode material prepared by this method.
[0038] Comparative Example 1
[0039] The molecular formula of the polyanionic sodium positive electrode material prepared in Comparative Example 1 is Na 3 Fe 3 (PO4) 3 The basic steps are the same as those in the embodiment, except that the sodium source is added in a one-step method. The specific preparation method comprises the following steps:
[0040] (1) 500 g of slag (referred to as ferrophosphorus slag) produced after lithium extraction from waste lithium iron phosphate battery black powder was taken, sulfuric acid with a concentration of 20% was added in an amount of nFe:nH=1:4, and stirred at 70°C and a stirring speed of 300 r / min for 3 h, and a leachate was obtained by solid-liquid separation; iron powder was added to the leachate for reaction within 30 min to remove copper, n iron powder (Fe): n leachate (Cu)=1.5:1, so that the trivalent iron in the system was completely reduced to divalent iron, and phosphorus-containing Fe was filtered out. 2+ filtrate.
[0041] (2) Phosphorus-containing Fe 2+ The filtrate was added with 10% hydrogen peroxide for 1 to 4 hours to oxidize all the divalent iron, among which n leachate (Fe 2+ ):nH 2 O 2 =1:0.7; phosphoric acid was added to adjust the system nFe:nP=1.05:1, ammonia was added to adjust the pH value to 1.8, and precipitation reaction was carried out at 30°C for 1h to obtain a suspension.
[0042] (3) The suspension is passed through a plate and frame filter press to obtain crude iron phosphate, which is then washed twice with an acid having a pH value of 1.2 and then washed twice with water to obtain crude iron phosphate from which aluminum has been removed.
[0043] (4) At room temperature, the crude iron phosphate obtained in step (3) is dispersed in deionized water with a solid-liquid ratio of 100 g / L; phosphoric acid is then added to adjust nP:nFe=3:3; the temperature is raised to 90°C and crystallized under stirring until the material turns white, aged for 2 hours, and separated to obtain an aged filter cake.
[0044] (5) Drying the aged filter cake obtained in step (4) at 120° C. for 6 h to obtain ferric phosphate dihydrate.
[0045] (6) Mixing ferric phosphate dihydrate with sodium carbonate and sucrose, adding water to control the solid content to 40%, stirring the mixture at a stirring rate of 100 to 300 r / min for 20 to 200 min to obtain a dispersed suspension; wherein the molar ratio of the added amount of sodium salt to the iron element in the ferric phosphate dihydrate is 3:3, and the added amount of the carbon source is 10% of the mass of the ferric phosphate dihydrate.
[0046] (7) The suspension described in step (6) is subjected to sand grinding, spray drying, and sintering to obtain a polyanionic sodium positive electrode material; wherein the sand grinding particle size is controlled to be 0.2-0.4 μm, and the sand grinding temperature is 40° C.; the inlet air temperature of the spray drying is 270° C., the exhaust air temperature is controlled to be 80° C., and the spray particle size is controlled to be 6-20 μm to obtain a spray material.
[0047] (8) Sintering the spray material described in step (7) under nitrogen protection at 500° C. for 10 h to obtain a polyanionic sodium positive electrode material.
[0048] Example 2
[0049] The molecular formula of the polyanionic sodium positive electrode material prepared in Example 2 is Na 2.9 Fe 2.9 V 0.1 (PO4) 3 The preparation method comprises the following steps:
[0050] (1) 600 g of slag (referred to as ferrophosphorus slag) produced after lithium extraction from waste lithium iron phosphate battery black powder was taken, and phosphoric acid with a concentration of 20% was added in an amount of nFe:nH=1:4, and stirred for 3 h at 70°C and a stirring speed of 300 r / min, and a leachate was obtained by solid-liquid separation; iron powder was added to the leachate and reacted within 30 min to remove copper, n iron powder (Fe): n leachate (Cu)=1.5:1, so that the trivalent iron in the system was completely reduced to divalent iron, and phosphorus-containing Fe was filtered out. 2+ filtrate.
[0051] (2) Phosphorus-containing Fe 2+ The filtrate was added with 10% hydrogen peroxide for 1 to 4 hours to oxidize all the divalent iron, among which n leachate (Fe 2+ ):nH2 O 2 =1:0.6; phosphoric acid was added to adjust the system nFe:nP=1.02:1, sodium hydroxide was added to adjust the pH value to 1.8, and a precipitation reaction was carried out at a temperature of 30°C for 1 hour to obtain a suspension.
[0052] (3) The suspension is filtered through a plate and frame filter press to obtain a crude sodium iron phosphate compound, which is then washed twice with an acid having a pH value of 1.2 and then washed twice with water to obtain a crude sodium iron phosphate compound from which aluminum has been removed.
[0053] (4) At room temperature, the crude sodium iron phosphate compound obtained in step (3) is dispersed in deionized water with a solid-liquid ratio of 100 g / L; then monoammonium phosphate and sodium acetate are added to adjust nP:nFe:nNa=3:2.9:0.5; the temperature is raised to 85°C and crystallized under stirring until the material turns white, and the aging reaction is carried out for 2 hours, and the aged filter cake is separated.
[0054] (5) Drying the aged filter cake obtained in step (4) at 120° C. for 6 h to obtain a sodium iron phosphate dihydrate compound.
[0055] (6) Mixing sodium ferric phosphate dihydrate compound with sodium acetate and ammonium metavanadate, adding water to control the solid content to 40%, stirring the reaction at a stirring rate of 100 to 300 r / min for 20 to 200 minutes to obtain a dispersed suspension; wherein the molar ratio of the added amount of sodium salt to the sodium element in the sodium ferric phosphate dihydrate compound is 2.5:0.5; and the molar ratio of the added amount of ammonium metavanadate to the iron element in the sodium ferric phosphate dihydrate compound is 0.1:3.
[0056] (7) The suspension described in step (6) is subjected to sand grinding, spray drying, and sintering to obtain a high-rate polyanion sodium positive electrode material; wherein the sand grinding particle size is controlled to be 0.2-0.4 μm, and the sand grinding temperature is 45° C.; the inlet air temperature of the spray drying is 270° C., the exhaust air temperature is controlled to be 80° C., and the spray particle size is controlled to be 6-20 μm to obtain a spray material.
[0057] (8) Sintering the spray material described in step (7) under nitrogen protection at 500° C. for 10 h to obtain a high-rate polyanion sodium cathode material.
[0058] Comparative Example 2
[0059] The molecular formula of the polyanionic sodium positive electrode material prepared in Comparative Example 2 is Na 2.9 Fe 2.9 V 0.1 (PO4) 3 The preparation method comprises the following steps:
[0060] (1) 600 g of slag (referred to as ferrophosphorus slag) produced after lithium extraction from waste lithium iron phosphate battery black powder was taken, and phosphoric acid with a concentration of 20% was added in an amount of nFe:nH=1:4, and stirred for 3 h at 70°C and a stirring speed of 300 r / min, and a leachate was obtained by solid-liquid separation; iron powder was added to the leachate and reacted within 30 min to remove copper, n iron powder (Fe): n leachate (Cu)=1.5:1, so that the trivalent iron in the system was completely reduced to divalent iron, and phosphorus-containing Fe was filtered out. 2+ filtrate.
[0061] (2) Phosphorus-containing Fe 2+ The filtrate was added with 10% hydrogen peroxide for 1 to 4 hours to oxidize all the divalent iron, among which n leachate (Fe 2+ ):nH 2 O 2 =1:0.6; phosphoric acid was added to adjust the system nFe:nP=1.02:1, ammonia was added to adjust the pH value to 1.8, and precipitation reaction was carried out at 30°C for 1h to obtain a suspension.
[0062] (3) The suspension is passed through a plate and frame filter press to obtain crude iron phosphate, which is then washed twice with an acid having a pH value of 1.2 and then washed twice with water to obtain crude iron phosphate from which aluminum has been removed.
[0063] (4) At room temperature, the crude iron phosphate obtained in step (3) is dispersed in deionized water with a solid-liquid ratio of 100 g / L; then monoammonium phosphate is added to adjust nP:nFe=3:2.9; the temperature is raised to 85°C and crystallized under stirring until the material turns white, aged for 2 hours, and separated to obtain an aged filter cake.
[0064] (5) Drying the aged filter cake obtained in step (4) at 120° C. for 6 h to obtain ferric phosphate dihydrate.
[0065] (6) Mixing ferric phosphate dihydrate with sodium acetate and ammonium metavanadate, adding water to control the solid content to 40%, stirring the mixture for 20 to 200 minutes at a stirring rate of 100 to 300 r / min to obtain a dispersed suspension; wherein the molar ratio of the amount of sodium salt added to the iron element in the ferric phosphate dihydrate is 2.9:2.9; and the molar ratio of the amount of ammonium metavanadate added to the iron element in the compound of sodium ferric phosphate dihydrate is 0.1:3.
[0066] (7) The suspension described in step (6) is subjected to sand grinding, spray drying, and sintering to obtain a polyanionic sodium positive electrode material; wherein the sand grinding particle size is controlled to be 0.2-0.4 μm, and the sand grinding temperature is 45° C.; the inlet air temperature of the spray drying is 270° C., the exhaust air temperature is controlled to be 80° C., and the spray particle size is controlled to be 6-20 μm to obtain a spray material.
[0067] (8) Sintering the spray material described in step (7) under nitrogen protection at 500° C. for 10 h to obtain a polyanionic sodium positive electrode material.
[0068] Example 3
[0069] The molecular formula of the polyanionic sodium positive electrode material prepared in Example 3 is Na 2.8 Fe 2.8 V 0.2 (PO4) 3 The preparation method comprises the following steps:
[0070] (1) 400 g of slag (referred to as ferrophosphorus slag) produced after lithium extraction from waste lithium iron phosphate battery black powder was taken, nitric acid with a concentration of 20% was added, and the amount of nitric acid added was nFe:nH=1:4. The mixture was stirred at 70°C and a stirring speed of 300 r / min for 3 h, and a leachate was obtained by solid-liquid separation. Iron powder was added to the leachate and the reaction was carried out within 30 min to remove copper, and n iron powder (Fe):n leachate (Cu) was 1.5:1, so that the trivalent iron in the system was completely reduced to divalent iron, and phosphorus-containing Fe was filtered out. 2+ filtrate.
[0071] (2) Phosphorus-containing Fe 2+ The filtrate was added with 10% hydrogen peroxide for 1 to 4 hours to oxidize all the divalent iron, among which n leachate (Fe 2+ ):nH 2 O 2 =1:0.5; phosphoric acid was added to adjust the system nFe:nP=1.1:1, sodium hydroxide was added to adjust the pH value to 2.0, and a precipitation reaction was carried out at a temperature of 20°C for 2h to obtain a suspension.
[0072] (3) The suspension is filtered through a plate and frame filter press to obtain a crude sodium iron phosphate compound, which is then washed twice with an acid having a pH value of 1.2 and then washed twice with water to obtain a crude sodium iron phosphate compound from which aluminum has been removed.
[0073] (4) At room temperature, the crude sodium iron phosphate compound obtained in step (3) is dispersed in deionized water with a solid-liquid ratio of 100 g / L; then monoammonium phosphate and sodium citrate are added to adjust nP:nFe:nNa=3:2.8:1.5; the temperature is raised to 85°C and crystallized under stirring until the material turns white, and the aging reaction is carried out for 2 hours, and the aged filter cake is separated.
[0074] (5) Drying the aged filter cake obtained in step (4) at 120° C. for 6 h to obtain a sodium iron phosphate dihydrate compound.
[0075] (6) Mixing sodium iron phosphate dihydrate compound with sodium citrate, glucose and ammonium vanadate, adding water to control the solid content to 40%, stirring the mixture at a stirring rate of 100 to 300 r / min for 20 to 200 min to obtain a dispersed suspension; wherein the molar ratio of the added amount of sodium salt to the sodium element in the sodium iron phosphate dihydrate compound is 1.5:1.5; and the molar ratio of the added amount of vanadium element in the ammonium vanadate compound to the iron element in the sodium iron phosphate dihydrate compound is 0.2:3.
[0076] (7) The suspension described in step (6) is subjected to sand grinding, spray drying, and sintering to obtain a high-rate polyanion sodium positive electrode material; wherein the sand grinding particle size is controlled to be 0.2-0.4 μm, and the sand grinding temperature is 40° C.; the inlet air temperature of the spray drying is 270° C., the exhaust air temperature is controlled to be 80° C., and the spray particle size is controlled to be 6-20 μm to obtain a spray material.
[0077] (8) Sintering the spray material described in step (7) under nitrogen protection at 500° C. for 10 h to obtain a high-rate polyanion sodium cathode material.
[0078] Comparative Example 3
[0079] The molecular formula of the polyanionic sodium positive electrode material prepared in Comparative Example 3 is Na 2.8 Fe 2.8 V 0.2 (PO4) 3 The preparation method comprises the following steps:
[0080] (1) 400 g of slag (referred to as ferrophosphorus slag) produced after lithium extraction from waste lithium iron phosphate battery black powder was taken, nitric acid with a concentration of 20% was added, and the amount of nitric acid added was nFe:nH=1:4. The mixture was stirred at 70°C and a stirring speed of 300 r / min for 3 h, and a leachate was obtained by solid-liquid separation. Iron powder was added to the leachate and the reaction was carried out within 30 min to remove copper, and n iron powder (Fe):n leachate (Cu) was 1.5:1, so that the trivalent iron in the system was completely reduced to divalent iron, and phosphorus-containing Fe was filtered out. 2+ filtrate.
[0081] (2) Phosphorus-containing Fe 2+ The filtrate was added with 10% hydrogen peroxide for 1 to 4 hours to oxidize all the divalent iron, among which n leachate (Fe 2+ ):nH 2 O 2 =1:0.5; phosphoric acid was added to adjust the system nFe:nP=1.1:1, ammonia was added to adjust the pH value to 2.0, and precipitation reaction was carried out at a temperature of 20°C for 2h to obtain a suspension.
[0082] (3) The suspension is passed through a plate and frame filter press to obtain crude iron phosphate, which is then washed twice with an acid having a pH value of 1.2 and then washed twice with water to obtain crude iron phosphate from which aluminum has been removed.
[0083] (4) At room temperature, the crude iron phosphate obtained in step (3) is dispersed in deionized water with a solid-liquid ratio of 100 g / L; then monoammonium phosphate is added to adjust nP:nFe=3:2.8; the temperature is raised to 85°C and crystallized under stirring until the material turns white, aged for 2 hours, and separated to obtain an aged filter cake.
[0084] (5) Drying the aged filter cake obtained in step (4) at 120° C. for 6 h to obtain ferric phosphate dihydrate.
[0085] (6) Mixing ferric phosphate dihydrate with sodium citrate, glucose and ammonium vanadate, adding water to control the solid content to 40%, stirring the mixture for 20 to 200 minutes at a stirring rate of 100 to 300 r / min to obtain a dispersed suspension; wherein the molar ratio of the added amount of sodium salt to the iron element in the ferric phosphate dihydrate is 2.8:2.8; and the molar ratio of the added amount of ammonium vanadate to the iron element in the ferric phosphate dihydrate is 0.2:3.
[0086] (7) The suspension described in step (6) is subjected to sand grinding, spray drying, and sintering to obtain a polyanionic sodium positive electrode material; wherein the sand grinding particle size is controlled to be 0.2-0.4 μm, and the sand grinding temperature is 40° C.; the inlet air temperature of the spray drying is 270° C., the exhaust air temperature is controlled to be 80° C., and the spray particle size is controlled to be 6-20 μm to obtain a spray material.
[0087] (8) Sintering the spray material described in step (7) under nitrogen protection at 500° C. for 10 h to obtain a polyanionic sodium positive electrode material.
[0088] Performance Testing
[0089] The sodium electric materials prepared in the above Examples 1-3 and Comparative Examples 1-3 were subjected to performance testing, and the results obtained are shown in Table 1 below.
[0090] Table 1 Electrical performance data of Examples 1 to 3 and Comparative Examples 1 to 3
[0091]
[0092]
[0093] It can be seen from Table 1 that the sodium-based positive electrode material prepared by the three-step method of adding a sodium source in the present invention has a 1C50 cycle discharge capacity and a 1C 50 cycle capacity retention rate that are better than those of the sodium-based positive electrode material prepared by the one-step method of adding a sodium source, thereby achieving the preparation of a high-rate polyanion sodium-based positive electrode material.
[0094] In addition, in addition to the above embodiments, the process parameters, raw materials used, and the amount of raw materials added in the preparation of high-rate polyanion sodium positive electrode materials of the present invention can achieve the same technical effect within the scope defined by the claims of the present invention, and thus the embodiments are no longer verified one by one. For example, the content of the acid solution added during acid leaching can also be nFe:nH=1:(4-6), and the amount of iron powder added can also be niron powder:nCu in the leaching solution=(1-3):1, etc.
Claims
1. A method for preparing a high-rate polyanion sodium cathode material based on recycling lithium iron phosphate, characterized in that: The steps include: (1) Acid leaching of the cathode powder in the waste lithium iron phosphate battery and solid-liquid separation to obtain a leachate, iron powder is added to the leachate, and the reaction is filtered to obtain phosphorus-containing Fe 2+ filtrate; (2) adding an oxidant to the filtrate for oxidation reaction, adjusting the molar ratio of Fe to P in the system to (1.02-1.1):1, adding sodium hydroxide solvent to adjust the pH value, and performing precipitation and aluminum removal reaction to obtain a suspension; filtering the suspension, acid washing and water washing to obtain a crude sodium iron phosphate compound; (3) dispersing the crude sodium iron phosphate compound in water, adding phosphate and sodium salt to adjust the molar ratio of P, Fe and Na to 3:(2.8-3):(0.5-1.5), then stirring and crystallizing at 70-100° C. until the material turns crystal white, and then aging for 1-3 hours, separating the aged filter cake, and drying to obtain the sodium iron phosphate dihydrate compound; (4) mixing sodium iron phosphate dihydrate compound with sodium salt, carbon source and vanadium source, adding water and stirring to obtain a dispersed suspension, and finally sand milling, spray drying and sintering to obtain a high-rate polyanion sodium positive electrode material; wherein the molar ratio of the added amount of the sodium salt to the sodium element in the sodium iron phosphate dihydrate compound is (1.5-2.5):(0.5-1.5).
2. The method for preparing a high-rate polyanion sodium positive electrode material based on recycling lithium iron phosphate according to claim 1, characterized in that: In step (1), the acid solution includes at least one of phosphoric acid, sulfuric acid, nitric acid or hydrochloric acid, and the amount thereof is nFe:nH=1:(4-6); the amount of iron powder added is niron powder:nCu in the leaching solution=(1-3):
1.
3. The method for preparing a high-rate polyanion sodium positive electrode material based on recycling lithium iron phosphate according to claim 1, characterized in that: In step (2), the amount of the oxidant added is n leachate (Fe 2+ ):nH2O2=1:(0.5~0.7).
4. The method for preparing a high-rate polyanion sodium positive electrode material based on recycling lithium iron phosphate according to claim 1, characterized in that: In step (2), the sodium hydroxide solvent is added to adjust the pH value to 1.6-2.0, and the precipitation aluminum removal reaction is carried out at 20-50° C. for 0.5-2 h.
5. The method for preparing a high-rate polyanion sodium positive electrode material based on recycling lithium iron phosphate according to claim 1, characterized in that: In step (3), the phosphate is monoammonium phosphate or phosphoric acid.
6. The method for preparing a high-rate polyanion sodium positive electrode material based on recycling lithium iron phosphate according to claim 1, characterized in that: In step (3) and step (4), the sodium salt is sodium carbonate, sodium acetate, sodium citrate, sodium oxalate, sodium bicarbonate, sodium sulfate, sodium chloride or sodium nitrate.
7. The method for preparing a high-rate polyanion sodium positive electrode material based on recycling lithium iron phosphate according to claim 1, characterized in that: In step (4), the added amount of the carbon source is 0 to 15% of the mass of the sodium iron phosphate dihydrate compound, and the carbon source is glucose, sucrose, starch, citric acid, oxalic acid or graphene.
8. The method for preparing a high-rate polyanion sodium positive electrode material based on recycling lithium iron phosphate according to claim 1, characterized in that: In step (4), the molar ratio of the added amount of the vanadium source to the iron element in the compound of sodium iron phosphate dihydrate is (0-0.2):3, and the vanadium source is ammonium vanadate or ammonium metavanadate.
9. The method for preparing a high-rate polyanion sodium positive electrode material based on recycling lithium iron phosphate according to claim 1, characterized in that: In step (4), the stirring time is 20 to 200 min, the stirring rate is 100 to 300 r / min; the sanding particle size is 0.2 to 0.6 μm, and the sanding temperature is 20 to 50° C.; the spray particle size is 6 to 20 μm, and the spray outlet temperature is 70 to 110° C.; the sintering temperature is 450 to 750° C., and the sintering time is 6 to 12 h.
10. A high-rate polyanion sodium positive electrode material prepared by the method of claim 1, characterized in that: The molecular formula of the sodium positive electrode material is Na 3-x Fe 3-x V x (PO4)3, where x=0~0.2.
Citation Information
Cited By
A sodium-ion battery nfpp positive electrode material prepared by value-added recycling of waste lithium iron phosphate and a method and application thereof
CN122540828A